Non-invasive diagnosis of esophageal varices after Baveno VI - Velázquez, Carlos Moctezuma; Abraldes, Juan G. (Turkish Journal of Gastroenterology, 2017)
Abstract A major complication of portal hypertension in patients with cirrhosis is the development of esophageal varices with the associated risk of variceal bleeding. Hence, the Baveno consensus on portal hypertension in its first five editions had recommended surveillance with periodic upper endoscopies in these patients to identify in a timely fashion the development of esophageal varices and initiate a primary prophylaxis strategy in those at a high risk of bleeding. For the first time, the Sixth Baveno Consensus on Portal Hypertension (Baveno VI) recommended using non-invasive tools to rule out the presence of varices with a high risk of bleeding. According to Baveno VI, surveillance endoscopy is not necessary for patients with “compensated advanced chronic liver disease” (cACLD) who have normal platelets (>150×109/L) and a liver stiffness measure (LSM) <20 kPa. In this review, we will briefly describe the currently available non-invasive methods to predict the presence of varices, such as serum tests, imaging, and elastography. We will also discuss the rationale that led to Baveno VI recommendation and describe the studies that have validated Baveno VI criteria after its publication. Finally, we will mention some potential caveats and suggest some areas for future research.